Impact of Creativity and Lifestyle on Customer Satisfaction in Event Planning Services: A Quantitative Study: Pengaruh Kreativitas dan Gaya Hidup terhadap Kepuasan Pelanggan pada Jasa Event Planning: Sebuah Studi Kuantitatif - Putri, Widya Yeza; Purwanto, Nuri (Indonesian Journal of Law and Economics Review, 2023)
This study investigates the influence of creativity and lifestyle on customer satisfaction in event planning services. Using a quantitative approach and explanatory method, data was collected from 100 consumers who had utilized event planning services over a six-month period. The analysis revealed that creativity significantly enhances consumer satisfaction, indicating that higher levels of creativity lead to increased satisfaction. Additionally, lifestyle was found to be a positive predictor of consumer satisfaction, highlighting that a higher lifestyle correlates with greater satisfaction in utilizing event planning services. These findings underscore the importance of creativity and lifestyle considerations in enhancing customer satisfaction within the event planning industry. Highlight: Creativity Amplifies Consumer Satisfaction: The study establishes a significant link between creativity and enhanced consumer satisfaction within event planning services, emphasizing the pivotal role of innovative approaches in service delivery. Lifestyle as a Positive Predictor: The research identifies lifestyle as a key factor influencing consumer satisfaction in event planning services, underscoring the importance of aligning services with the preferences and values of the target clientele. Implications for Event Planning Industry: These findings provide valuable insights for the event planning industry, highlighting the need to prioritize creativity and consider the lifestyle preferences of consumers to maximize overall satisfaction and competitiveness in the market. Keyword: Creativity, Lifestyle, Customer Satisfaction, Event Planning Services, Quantitative Approach